Analysis of Protein Level and Acceptability of Snow White Edamame Flour Substitution (Glycine max (L) Merrill) - Akbar, Abdul Azis; Wibowo, Nura'isyah Indah (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2023)
Edamame is a potential plant that is abundantly available in Indonesia, but its consumption level is not optimal, even though it has nutritional content such as protein, calcium, zinc, and phosphorus. The high protein content in edamame can be used to overcome stunting problems. Edamame can be processed into flour that can be used as an additional ingredient in putri salju cookies. Putri salju as a substitute for edamame flour is expected to be a high-protein additional food that is good for children's growth and development. This study aims to analyze the protein content and acceptability of putri salju as a substitute for edamame flour. This quasi-experimental study used a posttest-only control group design. Analysis of protein content using the kjeldahl method and acceptability using the hedonic test. The study population was edamame flour with SPP-PIRT and LPPOM-MUI specifications, and the acceptability test panelists were 56 students of SDN Ajung 1. The research sample was edamame flour (Hasil Bumiku) and 25 students as panelists. The research instruments included an informed consent form, hedonic test, and a protein content test result sheet. The results showed that there were differences in protein content (p-value 0.000) and the acceptability of color (p-value 0.001), aroma (p-value 0.001), taste (p-value 0.000), and texture (p-value 0.000) of putri salju. The best treatment was putri salju treatment X1 (10%). The recommended consumption of putri salju treatment X1 as additional food for children aged 12-24 months is 6 pieces per day. In conclusion, there are differences in protein content and the acceptability of color, aroma, taste and texture of putri salju, and the recommended consumption of putri salju is 6 pieces per day. Further research is expected to analyze the energy, carbohydrate, calcium, zinc, and phosphorus content and test the shelf life of putri salju.